ANALISIS PENANAMAN NILAI KEWIRAUSAHAAN MELALUI PROGRAM MARKET DAY DI SD MUHAMMADIYAH TOBOALI BANGKA SELATAN - Fuad, Chairul; Diana Pramesti; Sisi Pitriyana (Universitas Muhammadiyah Bangka Belitung, 2023)
The study aimed to analyze the entrepreneurial values through the implementation of market day on the students at SD Muhammadiyah Toboali. This study used a descriptive qualitative method. The research subjects were a teacher and 21 students of class VB. Data were collected through observation, classroom-teacher interviews, and student questionnaires. Data analysis was carried out through data reduction, data presentation, and conclusion. Triangulation was carried out to test the validity of the data. The results of the analysis on entrepreneurial values in the market day program which were carried out during class meetings, each class will carry out on different days. Entrepreneurial values that have grown from the market day such as: 1) the value of independence grows in VB class students by as much as 38.1% when students can carry out tasks without the help of others such as when preparing products for sale; 2) the value of creative growth for all of the students in VB class can be seen from giving a unique name so that buyers are interested; 3) the value of daring to take risks can be seen in class VB when the students dare to take risks if their products do not sell; 4) the value of action-oriented growth of the students in VB was 57.2%, it can be seen when students felt happy being appointed to market day activities; 5) the value of leadership was 28.5%, it can be seen when students coordinated one another during market day activities so that they were orderly; 6) the value of hard work of the students in the class of VB, can be seen when students carry out market day activities happily and earnestly.